2024
DOI: 10.1021/acs.joc.3c02032
|View full text |Cite
|
Sign up to set email alerts
|

Cinchona-Alkaloid-Derived NNP Ligand for Iridium-Catalyzed Asymmetric Hydrogenation of β-Keto Ester

Qian Xu,
Wenchang Gou,
Pinli Dai
et al.

Abstract: The Ir-catalyzed asymmetric hydrogenation of βketo esters with Cinchona-alkaloid-derived NNP ligands has been developed. β-Hydroxy esters of opposite configuration were afforded smoothly with 91.5−99.1 and 81.6−99.3% ee, respectively, using NNP L2 and L7 derived from quinidine and quinine separately even on the gram scale. The protocol for the preparation of β-hydroxy esters of opposite configuration by the simple conversion of ligand configurations offered further opportunities for the synthesis of biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Recently, Li [85] et al reported the Ir-catalyzed asymmetric hydrogenation of β-keto esters 42 with Cinchona-alkaloid-derived P,N,N-ligands L12. The protocol for the preparation of β-hydroxy esters of opposite configuration by the simple conversion of ligand configurations offered further opportunities for the synthesis of biologically active molecules and drugs (Scheme 44).…”
Section: Asymmetric Hydrogenation Of Keto Estersmentioning
confidence: 99%
“…Recently, Li [85] et al reported the Ir-catalyzed asymmetric hydrogenation of β-keto esters 42 with Cinchona-alkaloid-derived P,N,N-ligands L12. The protocol for the preparation of β-hydroxy esters of opposite configuration by the simple conversion of ligand configurations offered further opportunities for the synthesis of biologically active molecules and drugs (Scheme 44).…”
Section: Asymmetric Hydrogenation Of Keto Estersmentioning
confidence: 99%